Labor Activity of Convicts in Conditions of Humanization of Imprisonment in Late 18th — Early 21st Centuries (Western Siberia) - O. N. Naumenko; M. Sh. Almukhametova; M. G. Pinigin (Научный диалог, 2023)
The experience of attracting convicts to work in West Siberian prisons, including those located on the territory of the Arctic zone of Yugra in the late 18th — early 21st centuries, is considered. It is noted that this experience was introduced as part of the humanization of the penitentiary system according to the European model. The authors introduce the concept of “three-phase model” of humanization of the prison. The thesis is substantiated that in the history of Russia this model was implemented three times and necessarily included new principles for organizing the work of prisoners. The results of the last reform, which took place in 2010—2020 are compared with previous reforms and general patterns characteristic of Russia are identified. The purpose of the article is to determine the relationship between the model of work in places of detention and the stages of weakening / strengthening of political power. The study is carried out through the analysis of the organization of work of prisoners, since this factor is an indicator of the state of the law enforcement system, and it reflects the degree of stability of state power as a whole. The study concluded that in the conditions of Russia, the principles of organizing the work of prisoners should correspond to the ideas of justice that are characteristic of the Russian people. The authors argue that the “three-phase model” implemented several times for the humanization of the prison according to the European model always entails negative consequences for the Russian statehood.